Diagnostika a lécba organického hyperinzulinismu--zkusenosti u 105 pacientů - Skrha, J; Sváb, J; Krusina, L; Dusková, J; Hilgertová, J; Keil, R (Casopis lekaru ceskych, 2009)
BACKGROUND: Organic hyperinsulinism causes hypoglycaemia manifesting mainly in the fasting state. We summarize our experience with diagnosis and treatment of 105 patients with organic hyperinsulinism. METHODS AND RESULTS: The diagnosis was confirmed in all patients by spontaneous hypoglycemia and neuroglycopenic symptoms, both developed during fasting test. Endoscopic ultrasonography was the most reliable method for the insulinoma localization (77% of insulinomas confirmed by surgery in the same location within the pancreas), less positive results were obtained by digital subtraction angiography (29%) and still less was found by computed tomography (18%). The localization remains unclear in about 20-25% of insulinomas despite of combined different exploring techniques. Surgical removal of insulinoma by enucleation is the best way of treatment, in some cases laparoscopic removal is a method of choice. From total number of 95 surgically treated patients the successful removal of insulinoma was performed in 84 patients (88%) and another 3 had histopathology diagnosis of micronodular polyadenomatosis. CONCLUSIONS: Insulinoma was not found during surgery and subsequent thorough histopathology investigation of the whole resecate in 8 patients which have to be treated like other non-surgically treated patients by diazoxide together with diabetic diet.
Keywords: senioři; Hyperinsulinism; senioři nad 80 let; mladiství; Middle Aged; mužské pohlaví; nádory slinivky břišní; Adult; mladý dospělý; Insulinoma; Aged, 80 and over; Young Adult; ženské pohlaví; hyperinzulinismus; Humans; Pancreatic Neoplasms; lidé středního věku; dospělí; inzulinom; Female; Aged; Adolescent; lidé; Male